Contested womanhood: women's education and (re)production of gendered norms in rural Pakistani Muslim communities. Issue 4 (4th July 2018) - Khurshid, Ayesha; Saba, Alexis
ABSTRACT: In a world marred by the fears of religious extremism, Muslim women have become subjects of various global projects that aim to modernize 'traditional' Muslim societies through women's education and empowerment. Embedded in these discourses is an assumption that all educated Muslim women will empower themselves through challenging the 'oppressive' structures of their families and communities. This paper challenges these homogeneous narratives of education and empowerment through highlighting the complexities of educated women's daily lives in rural Pakistan. We situate the lived experiences of rural educated Pakistani women in global mainstream as well as in local historical narratives regarding the role and purpose of education for women. Our analysis reveals how the educated women participants' lives were shaped by a complex gendered hierarchy that facilitated educated women to take on new roles while simultaneously requiring them to maintain harmonious relationships with family and community members.